Year over year efficiencies of Bank Negara Malaysia: Data envelopment analysis versus stochastic frontier analysis - Mat Kasim, Maznah; Baten, Md Azizul; Ramli, Razamin (GBSE, 2016)
This paper examines Bank Negara Malaysia (BNM) twelve year to year efficiency levels by employing two competing frontier analyses namely Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA).The data covers a 12-year time periods from 2000 to 2012 except 2010, and five variables are considered where Net Profit (NP) and Loans & Advances (LA) are the outputs, while total assets, risk reserve and total deposit are the input variables.The results show that DEA gives the lowest average efficiency level at 0.936, while LA Stochastic Frontier model estimates the highest average year wise efficiency at 0.992, and the NP Stochastic Frontier model is the second highest (0.934).With all three efficiency averages of more than 0.9, BNM is at the positive phase to increase its outputs, which are NP and LA by using the same inputs.